Dampak Covid-19 Terhadap Stabilitas Nilai Saham Di Bursa Efek Indonesia (Blue Chip Periode 2016 – 2020) - Arum Cahya; Amelia Setyawati; Selfiah Selfiah; Farij Ibadil Maula; Moh Shabri (RISK : Jurnal Riset Bisnis dan Ekonomi, 2022)
This study aims to analyze the effect of the pandemic on price stability or stock value and analyze the analysis of the effect of changes in value on investor satisfaction during the pandemic. This study uses a qualitative method with a descriptive approach. The population in this study is the Blue Chips company, which is the Blue Chips company, totaling 10 companies for the 2018-2020 period. The data collection method in this study used observation, namely secondary data and stock exchange observations. The type of data used is the type of secondary data